Comparative study on the dynamics of real estate market price of apartments in Târgu Mures - Emil Nuţiu (Scientific Bulletin of the ''Petru Maior" University of Tîrgu Mureș, 2011)
The study presents an analysis of the causes which have contributed to the decline in real estate. There will be an analysis of housing market price dynamics of the apartments, with specific reference to the housing market in Tg Mureş, at the begining of the crisis compared with the current prices